Analisis Implementasi Perjanjian Trips dalam Perlindungan Hak Kekayaan Intelektual di Indonesia - Dean Putri Amelia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study analyzes the implementation of the Trade-Related Aspects of Intellectual Property Rights (TRIPs) Agreement in the Intellectual Property Rights (IPR) protection system in Indonesia. As a member of the World Trade Organization (WTO) since 1995, Indonesia is obliged to adopt TRIPs provisions into national law based on the principle of single undertaking. This obligation has prompted the government to harmonize IPR regulations through the enactment of more comprehensive laws, such as the Copyright Law, the Patent Law, and the Trademark and Geographical Indications Law. This harmonization aims to create legal certainty, encourage innovation, and ensure effective protection of the creative output of the community. In practice, the implementation of TRIPs in Indonesia still faces challenges, including high levels of copyright infringement, weak law enforcement, and Indonesia's position as a net importer of technology, which leads to dependence on protection standards that favor developed countries. In addition, international pressure in the implementation of TRIPs often reflects an imbalance of interests between developed and developing countries. Through normative legal analysis, this study finds that although Indonesia has significantly harmonized its regulations, the effectiveness of TRIPs implementation still depends heavily on strengthening law enforcement mechanisms and increasing national capacity in the field of technology and innovation.